The pregnancy police: conceiving crime, arresting personhood - Howard, Grace (Reproductive justice: a new vision for the twenty-first century, 2024)
Decades before the overturning of Roe v. Wade, pregnant people faced arrest and prosecution for supposed crimes against the fertilized eggs, embryos, and fetuses they gestated. The Pregnancy Police investigates the legal arguments undergirding these prosecutions and sheds much-needed light on the networks of health-care providers, social workers, and legal personnel participating in this ongoing surveillance and punishment of pregnant people. Drawing on detailed analyses of legislation, statements from prosecutors and law enforcement, and records from over a thousand arrest cases, Grace E. Howard traces the long history of state attempts to regulate and control people who have the capacity for pregnancy--from the early twentieth century's white supremacist eugenics to the end of Roe and the ever-increasing criminalization of abortion across the United States